La Cumparsita: una fuente de pleitos Contursi y Maroni vs. Matos Rodríguez - Montero Aroca, Juan (Pontificia Universidad Católica del Perú, 2016)
This article deploys Tango along with the lawsuits concerning to whom participated in the elaboration of “La Cumparsita” and its lyrics as a frame of reference for discussing about copyrights and intellectual property. In addition to giving an opinion about the procedure to arrive at the final solution related to the adjudication of the copyrights along its effects of that in each one of the beneficiaries, the author tell us a little bit of the process of creating this musical composition as well as the scope it had during its time.

El presente artículo utiliza al Tango, a los pleitos y personajes que participaron en la elaboración de La cumparista y sus letras, como marco referencial para hablar sobre los derechos de autor y la propiedad intelectual. Además de opinar acerca del procedimiento para llegar a la solución final acerca de la adjudicación de los derechos de autor y los efectos de esta en cada uno de los beneficiarios, el autor nos cuenta un poco sobre el proceso de creación de esta composición musical así como el alcance que tuvo en su momento.
La Cumparsita: a source of lawsuits Contursi and Maroni vs. Matos Rodríguez
Keywords: Tango; Copyright; Lawsuits; Intellectual Property; “La Cumparsita”; Arbitration; Tango; Derechos De Autor; Pleitos; Propiedad Intelectual; La Cumparsita; Arbitraje; https://purl.org/pe-repo/ocde/ford#5.05.00